Determination of Toxic Metals in Cephalopods from South Korea - Nho, Eun Yeong; Khan, Naeem; Choi, Ji Yeon; Kim, Jae Sung; Park, Kyung Su; Kim, Kyong Su (TAYLOR & FRANCIS INC, 2016)
This study determined lead, cadmium, arsenic, mercury, and aluminum in six cephalopod species commercially available to consumers in South Korea. The samples were prepared by microwave-assisted acid digestion and analyzed by inductively coupled plasma-mass spectrometry (ICP-MS) for As, Pb, and Cd and inductively coupled plasma-optical emission spectrometry (ICP-OES) for Al. Hg was determined by a direct mercury analyzer with furnace-gold amalgation. Linearity, sensitivity, precision, accuracy, and recovery measurements were performed for validation. The analytical results showed that the average concentrations of metals were in decreasing order of Al>As>Cd>Pb>Hg. Paroctopus dofleini contained relatively high concentrations of Pb (0.43 mg/kg) and As (14.6 mg/kg); Todarodes pacificus contained high Cd (15.0 mg/kg), whereas Al (40.4 mg/kg) was highest in Loligo beka. Using the guidelines specified by Korean Food Regulations, the United Nations, and the European Commission, we found that the concentrations of these metals in the cephalopods studied were low and did not pose any threat to consumers.
Keywords: FATTY-ACID-COMPOSITION; OCTOPUS-VULGARIS; TRACE-ELEMENTS; FISH; PRODUCTS; SPECTROMETRY; MOLYBDENUM; SPECIATION; CHROMIUM; SELENIUM